Effects of exposure to electromagnetic field from 915 MHz radiofrequency identification system on circulating blood cells in the healthy adult rat. Issue 1 (24th November 2017) - Kim, Hye Sun; Park, Jae Sung; Jin, Yeung‐Bae; Do Choi, Hyung; Kwon, Jong Hwa; Pack, Jeong‐Ki; Kim, Nam; Ahn, Young Hwan
Abstract : We investigated whether exposure to the 915 MHz radiofrequency identification (RFID) signal affected circulating blood cells in rats. Sprague–Dawley rats were exposed to RFID at a whole‐body specific absorption rate of 2 W/kg for 8 h per day, 5 days per week, for 2 weeks. Complete blood counts were performed after RFID exposure, and the CD4 + /CD8 + ratio was determined by flow cytometry. The number of red blood cells (RBCs) and the values of hemoglobin, hematocrit, and RBC indices were increased in the RFID‐exposed group compared with those in the cage‐control and sham‐exposed groups ( P  < 0.05). However, the RBCs and platelet numbers were within normal physiologic response ranges. The number of white blood cells, including lymphocytes, was decreased in RFID‐exposed rats. However, there was no statistically significant difference between the sham‐exposed and RFID‐exposed groups in terms of T‐cell counts or CD4 + /CD8 + ratio ( P  > 0.05). Although the number of circulating blood cells was significantly altered by RFID exposure at a whole‐body specific absorption rate of 2 W/kg for 2 weeks, these changes do not necessarily indicate that RFID exposure is harmful, as they were within the normal physiological response range. Bioelectromagnetics. 39:68–76, 2018. © 2017 Wiley Periodicals, Inc.